2011
DOI: 10.1007/s00253-011-3401-5
|View full text |Cite
|
Sign up to set email alerts
|

Biological detoxification of the mycotoxin deoxynivalenol and its use in genetically engineered crops and feed additives

Abstract: Deoxynivalenol (DON) is the major mycotoxin produced by Fusarium fungi in grains. Food and feed contaminated with DON pose a health risk to humans and livestock. The risk can be reduced by enzymatic detoxification. Complete mineralization of DON by microbial cultures has rarely been observed and the activities turned out to be unstable. The detoxification of DON by reactions targeting its epoxide group or hydroxyl on carbon 3 is more feasible. Microbial strains that de-epoxidize DON under anaerobic conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
166
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(172 citation statements)
references
References 106 publications
(132 reference statements)
3
166
1
2
Order By: Relevance
“…Several attempts to reduce DON levels through chemical means have been deemed impractical due to the associated costs or their detrimental effect on the final grain quality (Karlovsky et al ., 2016). The microbial detoxification of DON by various species has been demonstrated using a wide variety of microorganisms and been extensively reviewed (Karlovsky, 2011; Zhu et al ., 2016). Earlier reported mechanisms of DON microbial detoxification have focused on de‐epoxidation, transformation of the C3 carbon (or attached groups), or the complete mineralization of DON (Karlovsky, 2011; Zhu et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several attempts to reduce DON levels through chemical means have been deemed impractical due to the associated costs or their detrimental effect on the final grain quality (Karlovsky et al ., 2016). The microbial detoxification of DON by various species has been demonstrated using a wide variety of microorganisms and been extensively reviewed (Karlovsky, 2011; Zhu et al ., 2016). Earlier reported mechanisms of DON microbial detoxification have focused on de‐epoxidation, transformation of the C3 carbon (or attached groups), or the complete mineralization of DON (Karlovsky, 2011; Zhu et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The microbial detoxification of DON by various species has been demonstrated using a wide variety of microorganisms and been extensively reviewed (Karlovsky, 2011; Zhu et al ., 2016). Earlier reported mechanisms of DON microbial detoxification have focused on de‐epoxidation, transformation of the C3 carbon (or attached groups), or the complete mineralization of DON (Karlovsky, 2011; Zhu et al ., 2016). Reported modifications of C3 include oxidation and epimerization of the attached hydroxyl group, which was demonstrated to reduce toxicity (He et al ., 2015a,b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach includes fungal, microbial, and enzymatic degradation of mycotoxins. Several very recent reviews on this topic can be found in the literature to which the reader is directed for specific insights [84,118,119,127,128]. Despite the many publications on this topic, this promising approach is still at a research level and far from an immediate outcome and application in practice for mycotoxin detoxification of food at industrial level.…”
Section: Use Of Physical Chemical and Biological Decontaminating Mementioning
confidence: 99%
“…While researchers have studied numerous feed additives for this purpose, few have proven effective in reducing the negative effects of DON in pigs (Do¨ll and Da¨nicke 2004;Karlovsky 2011). The blend of yeast cells, bacteria and plant extracts would be efficient to mitigate the negative effect of Fusarium toxins on growth performance in poultry (Da¨nicke et al 2002;Ghareeb et al 2012) but not in pigs (Barnes et al 2010), whereas aluminosilicates were not able to mitigate adverse effects of trichothecenes in pigs (Do¨ll et al 2005).…”
mentioning
confidence: 99%